2014
DOI: 10.5572/ajae.2014.8.1.035
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Exposure and Health Risk of Polycyclic Aromatic Hydrocarbons (PAHs) via Public Facilities PM2.5, Korea (II)

Abstract: The purpose of the study is to evaluate the pollution level (gaseous and particle phase) in the public facilities for the PAHs, non-regulated materials, forecast the risk level by the health risk assessment (HRA) and propose the guideline level. PAH assessments through sampling of particulate matter of diameter ⁄ ⁄2.5 μm (PM 2.5 ). The user and worker exposure scenario for the PAHs consists of 24-hour exposure scenario (WIES) assuming the worst case and the normal exposure scenario (MIES) based on the survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It is located near the Gwangyang industrial complex, which is populated by large oil refineries and petrochemical manufacturing plants [ 9 , 10 ]. A number of studies have been conducted and reported that the levels of environmental air pollution—including nitrogen dioxide (NO 2 ), carbon monoxide (CO), ozone (O 3 ), dioxins, toxic metals, volatile organic compounds (VOCs), formaldehyde, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), and particulate matter (PM)—were significantly increasing in the atmosphere, soil, and aquatic environments in these industrial complexes, which have been most affected [ 11 , 12 , 13 ]. Several studies concluded that chronic exposure to low levels of hazardous pollutants were significantly related to adverse effects on respiratory and cardiovascular systems among the residents living closer to Gwangyang and Yeosu industrial complexes in Korea [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is located near the Gwangyang industrial complex, which is populated by large oil refineries and petrochemical manufacturing plants [ 9 , 10 ]. A number of studies have been conducted and reported that the levels of environmental air pollution—including nitrogen dioxide (NO 2 ), carbon monoxide (CO), ozone (O 3 ), dioxins, toxic metals, volatile organic compounds (VOCs), formaldehyde, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), and particulate matter (PM)—were significantly increasing in the atmosphere, soil, and aquatic environments in these industrial complexes, which have been most affected [ 11 , 12 , 13 ]. Several studies concluded that chronic exposure to low levels of hazardous pollutants were significantly related to adverse effects on respiratory and cardiovascular systems among the residents living closer to Gwangyang and Yeosu industrial complexes in Korea [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies did not provide a quantification of a large range of chemical pollutants and microbiological contamination. To the best of authors' knowledge, only one indoor air quality study has been performed in pharmacies [8], and none in general practitioner's offices.…”
Section: Introductionmentioning
confidence: 99%